NUCLEAR NIGHTMARE ! - Twiddy, Robin (King's Lynn, Norfolk : BookLife, 2019)
Discover what the world of tomorrow might be like if we don't solve the pollution problem of today. Polluted Planet examines the causes of pollution and what you can do to save the future. Real information about real ecological issues are explored through fun and quirky science fiction narratives.
For ages 7-9 years.
Keywords: Nuclear energy -- Juvenile literature. -- Environmental aspects; Pollution -- Juvenile literature